Tomato extract suppresses the production of proinflammatory mediators induced by interaction between adipocytes and macrophages. Issue 1 (2nd January 2015) - Kim, Young-il; Mohri, Shinsuke; Hirai, Shizuka; Lin, Shan; Goto, Tsuyoshi; Ohyane, Chie; Sakamoto, Tomoya; Takahashi, Haruya; Shibata, Daisuke; Takahashi, Nobuyuki; Kawada, Teruo
Abstract: Obese adipose tissue is characterized by enhanced macrophage infiltration. A loop involving monocyte chemoattractant protein-1 (MCP-1) and tumor necrosis factor-α (TNFα) between adipocytes and macrophages establishes a vicious cycle that augments inflammatory changes and insulin resistance in obese adipose tissue. Tomatoes, one of the most popular crops worldwide, contain many beneficial phytochemicals that improve obesity-related diseases such as diabetes. Some of them have also been reported to have anti-inflammatory properties. In this study, we focused on the potential protective effects of phytochemicals in tomatoes on inflammation. We screened fractions of tomato extract using nitric oxide (NO) assay in lipopolysaccharide (LPS)-stimulated RAW264 macrophages. One fraction, RF52, significantly inhibited NO production in LPS-stimulated RAW264 macrophages. Furthermore, RF52 significantly decreased MCP-1 and TNFα productions. The coculture of 3T3-L1 adipocytes and RAW264 macrophages markedly enhanced MCP-1, TNFα, and NO productions compared with the control cultures; however, the treatment with RF52 inhibited the production of these proinflammatory mediators. These results suggest that RF52 from tomatoes may have the potential to suppress inflammation by inhibiting the production of NO or proinflammatory cytokines during the interaction between adipocytes and macrophages. Graphical abstract: : Tomato extract suppresses the production of proinflammatory mediators induced by interaction between adipocytes and macrophages.